Use of Mother Tongue in EFL Classes of Secondary Schools In Jabodebek: Students' and Teachers' Perception - Pardede, Parlindungan (JET (Journal of English Teaching), 2018)
This study aims to investigate senior high school students and teachers’ perception of the use of Indonesian in their English classes. To achieve the objective, two sets of questionnaires were administered to gauge the perceptions of 556 students and 15 teachers of 10 senior high schools in Jabodebek (Jakarta, Bogor, Depok, and Bekasi). The findings revealed: (1) the majority of both students and teachers preferred to use Indonesian in their English classes; (2) they believed Indonesian is helpful in language skills development, language components learning, learning materials understanding and classroom interactions; (3) the students preferred the predominantly use of Indonesian, while the teachers preferred the predominantly use of English during the class hour; (4) the higher their grade, the higher amount of English the students would like to have in their English classrooms; and (5) teachers with longer teaching experience tended to expect the use of bigger proportion of Indonesian in English classrooms.